Strategic communication for youth awareness during a Covid-19 outbreak: when the target becomes the creator - Oliveira, Hernâni Zão; Lima, Helena (Technium Social Sciences Journal, 2025)
During Covid-19 pandemic, a communication campaign promoted by a municipality in Portugal was unable to modify the risk behaviour of teenagers in schools. With the increase in safety rules, the exhaustion of teenagers gave way to revolt and disrespect - students started to remain at the school gates without masks and sharing cigarettes among themselves. The “Every Day Counts” campaign was developed to fix the extremely top-down orientation of the first campaign and to increase the impact of target-oriented communication via local government. Based on a Manifesto to other schools, the students with deviant behaviours were invited to co-create this new initiative. Three complementary products were developed: an animated film; a set of physical billboards distributed throughout the city; and a collection of bracelets that the participants used to promote the campaign. The materials were shared by 80 schools and 7 of them asked for help to replicate the same participatory methodology with their students. Furthermore, reports of deviant behaviour at the municipal school became residual.